The Creative Process Encountered by Students and The Strategy Used By Lecturer in Fostering Students’ Creativity As Beginner Writer In Writing A Short Story - Komang Sas Dewiyanti; Kadek Sonia Piscayanti; Indah Aditiya Pratiwi (Indonesian Journal Of Educational Research and Review, 2020)
The current research investigated the creative process encountered by students and the strategy used by lecturer in fostering students’ creativity as beginner writer in writing a short story. This research was a case study. Data were collected through interview guide. The obtained data were analyzed qualitatively. The recorded stages of creative process encountered by students were seven namely preparation, planning, incubation, beginning, flowing, breakthrough, and on title, and strategies used by lecturer to foster creativity were eight namely allow time to creative, keep an open mind, rewarding creative idea, lead by example, allowing mistakes, imagining other viewpoints, exploring environment, and thinking process. The research findings are as follows; 1). All of the students had passed through the stages of creative process in varied way, 2). Most of students had no passed through the planning stage, 3). There was only one student had passed through the planning stage, 4) The lecturer had applied all the eight elements as strategies in fostering students’ creativity.